2019
DOI: 10.1186/s13104-019-4634-0
|View full text |Cite
|
Sign up to set email alerts
|

Height estimation based on second cervical vertebra measured using three-dimensional computed tomographic scanning in Iranian adults

Abstract: Objectives The cervical vertebrae are more durable than other skeletal components, and therefore may be the only remnants of a dead body. The present study aims to investigate the role of several linear dimensions of the second cervical vertebrae measured by Three-Dimensional Computed Tomographic Scanning (3D CT Scan) in height estimation of Iranian adult population. In this cross-sectional study, height determination was performed by measuring 15 indexes of the second cervical vertebrae. Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
2
0
3
Order By: Relevance
“…They concluded that the size of the C2 may be useful for height estimation [11]. In another study on height estimation using C2 measured using 3D-computed tomographic scanning in Iranian adults, the accuracy of linear dimensions of C2 vertebrae in the estimation of the body height of the Iranian adult was shown [12].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the size of the C2 may be useful for height estimation [11]. In another study on height estimation using C2 measured using 3D-computed tomographic scanning in Iranian adults, the accuracy of linear dimensions of C2 vertebrae in the estimation of the body height of the Iranian adult was shown [12].…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism is based on their shapes and sizes, according to various studies (27). They have been used for stature estimation (28). Their correlation with age has attracted a lot of attention.…”
Section: Discussionmentioning
confidence: 99%
“…Ainda, o formato geral de C2 se altera com a idade 8 . E há correlação entre várias de suas medidas com a estatura 9,10 .…”
Section: Introductionunclassified
“…Trabalhos utilizando medidas e características morfológicas de C2 na definição do PB indicaram grande heterogeneidade em sua aplicação prática 4,9,11 . Pesquisas feitas em populações distintas tendem a encontrar graus diferenciados de dimorfismo sexual 5,11 .…”
Section: Introductionunclassified
See 1 more Smart Citation